OPTIMASI SIFAT MEKANIS KEKUATAN TARIK BAJA ST 50 DENGAN PERLAKUAN GAS CARBURIZING VARIASI HOLDING TIME UNTUK PENINGKATAN MUTU BAJA STANDAR UJI ASTM A370 - Lesmanah, Unung; Marsyahyo, Eko; Vitasari, Prima (Jurnal MEKANIKAL, 2013)
ST 50 steel as a common engineering material, it can be optimized using gas carburizing treatment in Fluidized Bed Furnaces. Gas as carburizing media in the fluidied bed with vaned by holding time variation such as 1 hour, 2 hours, 3 hours, 4 hours, and 5 hours. The holding time variation is to be intern of mechanical properties of the steel. Optimized value of mechanical properties ST 50 was actived in 3 hours of the treatment, it found average of tensile strength 651,7 MPa. The results above were based on A370 ASTM standar. From SEM (Scanning Electron Microscope), fracture model also showed from SEM that the steel has hard and brittle fracture. It can be concluded that optimized steel using gas carburizing treatment shows significant improve of mechanical properties from steels.